Circulating Vascular Growth Factors and Magnetic Resonance Imaging Markers of Small Vessel Disease and Atrophy in Middle-Aged Adults - Raman, Mekala R; Himali, Jayandra J; Conner, Sarah C; DeCarli, Charles; Vasan, Ramachandran S; Beiser, Alexa S; Seshadri, Sudha; Maillard, Pauline; Satizabal, Claudia L (Stroke (1970), 2018)
Background and Purpose- Little is known about associations between vascular growth factors and magnetic resonance imaging (MRI) markers in midlife. We investigated the association of serum VEGF (vascular endothelial growth factor), Ang2 (angiopoietin 2), sTie2 (soluble tyrosine kinase with immunoglobulin-like and EGF-like domains 2), and HGF (hepatocyte growth factor) concentrations with MRI markers of brain aging in middle-aged adults. Methods- We evaluated 1853 participants (mean age, 46±9 years; 46% men) from the Framingham Heart Study. Serum growth factor concentrations were measured using standardized immunoassays. Outcomes included total brain, cortical and subcortical gray matter, white matter, cerebrospinal fluid, and white matter hyperintensity volumes derived from MRI; as well as fractional anisotropy in white matter tracts from diffusion tensor imaging. We related VEGF, Ang2, sTie2, and HGF to MRI measures using multivariable regression models adjusting for vascular risk factors. We tested for interactions with APOE (apolipoprotein E) genotype and CRP (C-reactive protein). Results were corrected for multiple comparisons. Results- Higher sTie2 was associated with smaller total brain (estimate by SD unit±SE=-0.08±0.02, P=0.002) and larger white matter hyperintensity (0.08±0.02, P=0.002) volumes. Furthermore, higher Ang2 (0.06±0.02, P=0.049) and HGF (0.09±0.02, P=0.001) were associated with larger cerebrospinal fluid volumes. Finally, higher Ang2 was associated with decreased fractional anisotropy, in APOE-ε4 carriers only. Conclusions- Vascular growth factors are associated with early MRI markers of small vessel disease and neurodegeneration in middle-aged adults.